Image-Based Fast Finite-Time Target Tracking Control of Onboard Inertially Stabilized Camera Platform - Sun, Xunhong; Zhu, Wenwu; Du, Haibo; Chen, Weile; Chen, Chih-Chiang (IEEE transactions on industrial electronics (1982), 2024)
In this article, we investigate the problem of fast finite-time target tracking control of the inertially stabilized platform (ISP) with a camera that mounted on a mobile robot. At first, the kinematics of the onboard ISP target tracking system is established by the geographic coordinate and pinhole camera model, which includes the state-dependent uncertainties and external disturbances. Then, based on the image information captured by camera, a continuous image-based fast finite-time control algorithm is designed for target tracking. Rigorous analysis proves that the target can be tracked at the center of camera's view in finite time in the absence of disturbances. In the presence of disturbances, the tracking error can converge to a region around the origin in finite time. Simulation and experimental comparisons are presented to confirm the efficiency of the proposed method.